Probing Electron Excitation Characters of Carboline-Based Bis-Tridentate Ir(III) Complexes - Jie Yan; Ze-Lin Zhu; Chun-Sing Lee; Shih-Hung Liu; Pi-Tai Chou; Yun Chi (Molecules, 2021)
In this work, we report a series of bis-tridentate Ir(III) metal complexes, comprising a dianionic pyrazole-pyridine-phenyl tridentate chelate and a monoanionic chelate bearing a peripheral carbene and carboline coordination fragment that is linked to the central phenyl group. All these Ir(III) complexes were synthesized with an efficient one-pot and two-step method, and their emission hue was fine-tuned by variation of the substituent at the central coordination entity (i.e., pyridinyl and phenyl group) of each of the tridentate chelates. Their photophysical and electrochemical properties, thermal stabilities and electroluminescence performances are examined and discussed comprehensively. The doped devices based on [Ir(cbF)(phyz1)] (Cb1) and [Ir(cbB)(phyz1)] (Cb4) give a maximum external quantum efficiency (current efficiency) of 16.6% (55.2 cd/A) and 13.9% (43.8 cd/A), respectively. The relatively high electroluminescence efficiencies indicate that bis-tridentate Ir(III) complexes are promising candidates for OLED applications.